Madu Sebagai Dressing Pada Penyembuhan Ulkus Diabetikum - Cassa Victoria regia Divandra (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by an increase in blood sugar level (hyperglycemia) resulting from defects in insulin secretion, insulin action, or both. The most common complications of patients with DM are diabetic ulcers. Diabetic foot ulcer healing is needed to prevent infection and amputation risk. Dressing treatment in diabetic foot ulcer healing can be done by using a traditional treatment such as honey. Objective: To find out more about the efficacy of honey as dressing treatment in diabetic ulcer healing. Methods: Using literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results: Honey has anti-bacterial, anti-viral, anti-fungal, anti-oxidant and anti-inflammatory properties and acts to maintain moisture balance at the site of the wound and also has a protective barrier to minimize contact of wound and infectious agents. The use of honey as a dressing treatment has proven to be effective and shorten the healing period of diabetic ulcers. Conclusion: The use of honey is effective as a dressing treatment for diabetic foot ulcer healing.